6j(j-8)=0

Simple and best practice solution for 6j(j-8)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6j(j-8)=0 equation:


Simplifying
6j(j + -8) = 0

Reorder the terms:
6j(-8 + j) = 0
(-8 * 6j + j * 6j) = 0
(-48j + 6j2) = 0

Solving
-48j + 6j2 = 0

Solving for variable 'j'.

Factor out the Greatest Common Factor (GCF), '6j'.
6j(-8 + j) = 0

Ignore the factor 6.

Subproblem 1

Set the factor 'j' equal to zero and attempt to solve: Simplifying j = 0 Solving j = 0 Move all terms containing j to the left, all other terms to the right. Simplifying j = 0

Subproblem 2

Set the factor '(-8 + j)' equal to zero and attempt to solve: Simplifying -8 + j = 0 Solving -8 + j = 0 Move all terms containing j to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + j = 0 + 8 Combine like terms: -8 + 8 = 0 0 + j = 0 + 8 j = 0 + 8 Combine like terms: 0 + 8 = 8 j = 8 Simplifying j = 8

Solution

j = {0, 8}

See similar equations:

| 3r=8/6 | | 4c+4=17 | | 4x-16=8x-40 | | -6/9c=16 | | 5(-1)-2y=11 | | 4x+49=2517 | | y-2=-3/4(x-4) | | 7.9x-1.5=22.2 | | 3-7x+8x+5=9x+13-19x | | 1/2n=15 | | (2x+7)2=2517 | | y+2(4)=3 | | x(x-3)(x-5)= | | 6=2/3y | | y+2(-3)=3 | | 8m=70.00 | | 2x43/8 | | -5y-100x+8=0 | | 14-12x+39x-18x=256-60y-100 | | 4x-16/4 | | x^2+y^2+12x-26y+169=0 | | 25x=20x | | -3/2(x-1/2)1/5-5x | | -100y-5x+8=0 | | 115+g=65 | | 12w+15r=39.87 | | 14-12x+39x-18x=256-60x-100 | | (y-7)squared=3 | | 7x-7-9x+10=2+3x | | 1000=25+j | | 35+h=45 | | 5r^2-44r+120=-33+11r |

Equations solver categories